Pengaruh Fear of Missing Out (Fomo) dan Gaya Hidup terhadap Perencanaan Keuangan Pribadi dengan Literasi Keuangan sebagai Variabel Moderasi: Studi Kasus pada Generasi Z di Kota Medan - Ade Ulfa Safira Hasibuan; Atika Atika; Purnama Ramadhani Silalahi (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2026)
This study aims to analyze the influence of Fear of Missing Out (FoMO) and lifestyle on personal financial planning of Generation Z in Medan City with financial literacy as a moderating variable. Generation Z has unique characteristics, including a tendency to exhibit consumptive behavior influenced by technology and social media, which is often reinforced by feelings of FoMO. The type of research used in this study is quantitative research. By using data collection techniques with survey or questionnaire methods. The results of this study show that the Fomo value variable (X1) has a calculated t value of (3.427). This value is greater than the t table value of 1.985. This can be interpreted that Fomo (X1) has a significant effect on Financial Planning, and the significant value of the t test is 0.004 <0.05, so the first hypothesis is accepted. The Lifestyle value variable (X2) has a calculated t value of (5.976). This value is greater than the t table value of 1.985. This can be interpreted as meaning that Lifestyle (X2) has a significant effect on Financial Planning, and the t-test significance value is 0.021 <0.05, thus the second hypothesis is accepted. The interacted variables of FoMo and Financial Literacy obtained a calculated t-test result of 2.259>t-table 1.985 and have a significance value of 0.005 <0.05. The interacted variables of Lifestyle and Financial Literacy obtained a calculated t-test result of 9.581>t-table 1.985 and have a significance value of 0.001 <0.05.